A Study on the Influence of Corporate Actions on Share Prices of Selected Companies from NSE - Lazar, D.; G., Pramod (Indian Journal of Finance, 2010)
We are daily seeing fluctuations in share prices in the stock markets. These fluctuations are due to various reasons. One of the main causes for the fluctuations in share price is due to the Corporate Actions of companies. These corporate actions can influence the shareholders. Shareholders can take the corporate actions in a positive way or negative way. On the basis of Corporate Actions, the investors make a judgment on the future performance of the companies. On the basis of this judgment, investors buy or sell securities. As a result, fluctuations in the share prices occur. Distributions of dividend/interest, issue of rights/bonus shares, issue of fresh securities by issuers, splits, consolidations, hive-off, warrants, mergers, de-mergers, acquisitions etc. made by the companies are called corporate actions. Corporate Actions are essential for all companies. Corporate Actions are necessary for the existence, business strategies, business techniques and for making profits. It is a comprehensive source for understanding a major component of operational processing. The impact of corporate actions are : a) Return profits to shareholders, b) Influence the share price: c) Corporate Restructuring: Examples of Corporate Actions are: Announcement to hold Annual General Body Meeting, Bonus issue, Dividend, Financial Results, Increase in Production Capacity, Introduction of New Product, Leadership changes, Meeting of Board of Directors, Mergers&Acquisitions, Net Profit, Shifting of Registered Office and Starting of New Office. An attempt is made in this study to see whether corporate actions influence the share price or not. For this study, 80 companies listed in the BSE were considered and twelve corporate actions were identified. Wilcoxon Matched Pairs Test was used to see the influence of Corporate Actions on Share Prices.